Assessment of psychological testing in the Philippines focus on industries and national education - Ramos, Exaltacion C. (Philippine Journal of Psychology, 1977)
Two areas of psychological testing are surveyed, namely industrial testing and national-education testing, for testing-related issues. This paper calls attention to the relative absence of efforts in test construction and test validation, despite the great actiyity in psychological testing. The need to upgrade the competence level and to define the responsibilities of psychologists involved in psychological testing is heavily underscored.